Optical and electronic activities of biobased films of chitosan/POTE containing gold nanoparticles: Experimental and theoretical analyses. (November 2018) - Méndez-López, M.; Moreno-Serna, V.; Inostroza-Rivera, R.; Ramos, A.; Molero, L.; Bonardd, S.; Diaz Diaz, D.; Leiva, A.; Saldías, C.
Graphical abstract: Highlights: The incorporation of POTE and gold nanoparticles decrease the optical band gap compared to bare chitosan film. The incorporation gold atom trends to vary of electronic density and electrostatic potential of the FMOs. The surface potential is slightly enhanced for CS/POTE/AuNPs films in comparison to that of CS/POTE films, and electronic activity displays a better distribution on the film surfaces. Notable changes were revealed in the topography and crystallinity of the films and in the size and shape of gold nanoparticles. Abstract: Biobased films consisting of blends of chitosan with poly(octanoic acid 2-thiophen-3-yl-ethyl ester) (POTE), a conducting polymer, and gold nanoparticles (AuNPs) were prepared, and their thermal, morphological and surface potential properties were studied. POTE was dissolved in THF and mixed with an acidified aqueous solution containing chitosan to obtain chitosan/POTE (CS/POTE) films by solution casting. To produce gold nanoparticles in the CS/POTE films (i.e., CS/POTE/AuNP films), an aqueous solution of KAuCl4 salt at fixed concentration was added to the initial chitosan solution. The fabricated biobased films were characterized by spectroscopic techniques (FT-IR and UV–visible), thermogravimetry, contact angle analysis, polarized light microscopy (PLM), field emission scanning electron microscope (FE-SEM) and scanning Kelvin probe force microscopy (SKPFM). The effects of varying POTE composition and the presence of gold nanoparticles in the films were analyzed. For example, the results indicated the existence of interactions between chitosan and POTE, and LPM studies revealed a predominantly amorphous nature of these biobased films. In addition, the optical and surface potential behaviors of the films were examined by UV–visible and KPFM techniques. From the UV–visible spectra, the optical band gaps were estimated for the samples, and their surface potential maps exhibited differences according to the composition of POTE and the presence of AuNPs. Finally, theoretical electronic calculations provided insight into the contributions of POTE and gold nanoparticles to the electronic activity of the films.